Heros or Schmucks?: Implications of the Hero Narrative for Gig Workers During the CoVid-19 Pandemic - Cameron, Lindsey D.; Fekete, Jordan Nye (2020)
ABSTRACT Overnight the pandemic has turned luxury services into essential services. Nowhere is this more evident than in food delivery where grocery shoppers have been dubbed ‘heros’ by the media and customers alike. Yet these workers encounter persistent precarious work conditions as they labor under invasive technology, fickle customers, and ever-changing platform rules. Drawing on a qualitative field study, including interviews, digital artifacts, forum posts, and newspaper articles, of grocery shoppers during the pandemic, we explore how individuals construct narratives of their work and the outcomes of said narratives. We begin by describing the construction of the hero narrative through media, customer interactions, and the platform and how workers either accept, reject, or contextualize the hero narrative. Our preliminary analysis suggests these responses to the hero narrative result in different strategies for engaging with the work and outcomes. This study has implications for literature in narrative construction, meaning-making, gig work, and precarious labor. Keywords algorithm, gig economy, narrative, essential workers, platform-based work, precarious work, coronavirus pandemic ABOUT THE AUTHOR/S Lindsey D. Cameron University of Pennsylvania ldcamer@wharton.upenn.edu "Lindsey D. Cameron is an assistant professor of management at the Wharton School at the University of Pennsylvania. Her research focuses on how changes in the modern workplace (e.g., algorithms/machine learning, short-term employment contracts, variable pay) affect work and workers. Her website is www.lindseycameron.com Jordan Nye Fekete University of Pennsylvania Jordan Nye Fekete is a research associate affiliated with the University of Pennsylvania and is interested in the creation, application, and impact of narratives. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).